Cover Picture: DNA Origami Seesaws as Comparative Binding Assay (ChemBioChem 12/2016). (17th June 2016) - Nickels, Philipp C.; Høiberg, Hans C.; Simmel, Stephanie S.; Holzmeister, Phil; Tinnefeld, Philip; Liedl, Tim
Abstract : The cover picture shows the concept of a nanoscopic weighing balance, which is used to measure differences in binding energy. The hybridization of competing DNA binding pairs was studied by using a self‐assembled DNA origami structure that acts as such a nanoscopic weighing balance. Changing the relative binding energies of the DNA binding pairs tips the scale towards the side with the higher number of hybridized DNA duplexes. Image by Christoph Hohmann, Nanosystems Initiative Munich (NIM). More information can be found in the communication by P. C. Nickels, T. Liedl et al. onpage 1093 in Issue 12, 2016 (DOI:10.1002/cbic.201600059 ).